Comparison of streptozotocin-induced diabetes at different moments of the life of female rats for translational studies - Sinzato, Yuri K [UNESP]; Klöppel, Eduardo [UNESP]; Miranda, Carolina A [UNESP]; Paula, Verônyca G [UNESP]; Alves, Larissa F [UNESP]; Nascimento, Lívia LS; Campos, Ana Paula [UNESP]; Karki, Barshana; Hampl, Václav; Volpato, Gustavo T; Damasceno, Débora Cristina [UNESP] (SAGE Publications, 2021)
Animal models are widely used for studying diabetes in translational research. However, methods for induction of diabetes are conflicting with regards to their efficacy, reproducibility and cost. A comparison of outcomes between the diabetic models is still unknown, especially full-term pregnancy.To understand the comparison, we analyzed the streptozotocin (STZ)-induced diabetes at three life-different moments during the neonatal period in Sprague–Dawley female rats: at the first (D1), second (D2) and fifth (D5) day of postnatal life. At adulthood (90 days; D90), the animals were submitted to an oral glucose tolerance test (OGTT) for diabetic status confirmation. The diabetic and control rats were mated and sacrificed at full-term pregnancy for different analyses. Group D1 presented a higher mortality percentage after STZ administration than groups D2 and D5. All diabetic groups presented higher blood glucose levels as compared to those of the control group, while group D5 had higher levels of glycemia compared with other groups during OGTT. The diabetic groups showed impaired reproductive outcomes compared with the control group. Group D1 had lower percentages of mated rats and D5 showed a lower percentage of a full-term pregnancy. Besides that, these two groups also showed the highest percentages of inadequate fetal weight. In summary, although all groups fulfill the diagnosis criteria for diabetes in adult life, in our investigation diabetes induced on D5 presents lower costs and higher efficacy and reproducibility for studies involving diabetes-complicated pregnancy.
Keywords: diabetes; fetus; glucose intolerance; hyperglycemia; Pregnancy